PENGGUNAAN ALAT PERMAINAN EDUKATIF (APE) DARI BOTOL PLASTIK DAN KORAN BEKAS UNTUK MENINGKATKAN KREATIFITAS AUD - Zikra Hayati (AWLADY : Jurnal Pendidikan Anak, 2019)
The aims of research to find out the development of early childhood creativity by using APE (Educational Playing) made by secondhand thing in RA Al-Ihsan Tgk Chik in Adan and to find out the types of APE that can be used to enhance early childhood creativity. Furthermore, The research was conducted because there are some problems indicate that early childhood has low development in creativity ability, teacher who have not used variety of APE, that impact for the children that less motivated, bored so that make less response for creativity development and activities in the class. The activities running in teaching and learning is not show that activities make stimulate children to think creatively, that is concluded from several creativity indicators are: the teacher has not made learning activities in to express children ideas, the child in RA has not been accustomed to creating something new, either to benefit secondhand thing use to create some APE. The type of research is classroom action research (CAR), the subject is early childhood, namely 6 children in grade A in RA Al-Ihsan Tgk Chik in Adan, in Pidie. Data collection techniques with Observation and Documentation. The results show that: (1) there is an enhancing children's creativity through APE from using second hand thing, as show that the percentage increase in the first cycle in the category of MB (Start to Grow) that is 45.83% and that was increase in Cycle II which was in BSB category (Developing Very Good) a percentage of 76.04%. Based on the data analysis it can be concluded that using APE from second hand thing can develop children creativity, from MB category (Start Developing) that is 45.83% and to BSB category (Very Good Developing) which is a percentage of 76, 04%. (2) The type of APE that used to improve children creativity in RA Al-Ihsan Tgk Chik in Adan, namely the type of APE that can develop aspects creative, namely: APE types of animals from plastic bottles and APE Geometry shapes and Numbering that is created by newspaper.